Auditory Processing in Stuttering Children: Behavioral and Electrophysiological Assessments - Gregory, Letícia; Sanfins, Milaine Dominici; Skarzynski, Piotr Henryk; Rosa, Rafael Fabiano Machado; Zen, Paulo Ricardo Gazzola; Sleifer, Pricila (International Archives of Otorhinolaryngology, 2025)
Introduction Stuttering is a human communication disorder characterized by involuntary interruptions to speech flow. Electrophysiological tests and behavioral evaluations allow the neuroaudiological processes involved in stuttering to be investigated.Objective To investigate group differences in the central auditory system using long-latency auditory evoked potentials, cognitive potentials, and behavioral assessments in children who stutter and compare them with fluent children.Methods We assessed 18 children with stuttering and compared them with a control group of 18 children without speech or language impairment. All children were evaluated with pure tone and speech audiometry, acoustic immittance measures, brainstem auditory evoked potentials, long latency auditory evoked potentials, cognitive potentials, and behavioral tests of auditory processing – Random Gap Detection Test (RGDT), Dichotic Digit Test (DDT); Duration Pattern Test (DPT); Pediatric Speech Intelligibility (PSI); and Masking Level Difference (MLD). The Scale of Auditory Behaviors (SAB) questionnaire was also applied.Results Children who stuttered had longer latencies of the P2 and P3 waves compared with the fluent group. There was no difference in P2 amplitudes, but there was a smaller P3 amplitude in children who stuttered, and they also showed significant alterations in the DDT and DPT. Furthermore, an association was found between increased P2 and P3 latency and SAB scores.Conclusion The present study indicates that children who stutter tend to have decreased auditory ability in terms of central auditory processing, and this shows up psychophysically and on the SAB questionnaire.
Keywords: stuttering; event-related potentials; P300; hearing; children; auditory evoked potentials